The evaluation of curcumin and analogues as potential inhibitors of the urease enzyme - Araujo, Débora Pereira; Silva, Emanuel Henrique da (Brazilian Journal of Production Engineering, 2021)
Ureases are enzymes that catalyze the hydrolysis of urea into carbon dioxide, ammonia and water. The hydrolysis of urea plays an important role on nitrogen cycle, once it provides such element for the growth of microorganisms and plants. However, the excessive action of the urease leads to several problems in living microorganisms, and it can cause economic and environmental damages as well. Urease inhibitors can be a good alternative for the treatment of diseases caused by pathogenic microorganisms, which are dependents on the urease enzyme. The Curcumin, a natural product from the curcuma longa, known in Brazil as saffron, has a structure capable of complexing metals, which makes it a potential inhibitor of metalloproteins just like the urease. For such reason, this work aimed to evaluate the potential of interaction of the curcumin and eleven analogues with the active site of the urease enzyme, using the Autodock and Mopac2016 programs for that. Based on the results, it was observed that nine compounds showed a better interaction with the active site of the urease enzyme when compared to the urea substrate, presenting then binding energies between -7,24 and -5,12 kcal/mol, while the urea presented such energy equals to -4,10 kcal/mol. The curcumin got the fifth position by presenting a binding energy equals to -6,21 kcal/mol, demonstrating a greater potential for being used as urease enzyme inhibitor.
Keywords: Curcumin; urease inhibitor; docking molecular